Pressure Ulcers In Palliative home Care Patients: Prevalence And Characteristics - Ana Carolina de Castro Mendonça Queiroz; Dálete Delalibera Corrêa de Faria Mota; Maria Marcia Bachion; Ana Cássia Mendes Ferreira (SciELO, 2014)
Persons in palliative care develop pressure ulcers (PU) as death approaches, but the extent of the problem is still unknown. The objectives were to identify the prevalence of pressure ulcers in people with cancer in palliative home care, compare the socio-demographic and clinical profile of patients with and without pressure ulcers, and analyze the characteristics of the ulcers. This descriptive, cross-sectional study included 64 people with advanced cancer in palliative home care. Twelve of them (18.8%) had PU, of whom 75.0% were men. The participants had one to three PU, amounting to 19 lesions, 89.4% of those developed at home and 47.4% at stage 3. The presence of PU was higher among those who had a history of previous wound. PU consisted of a significant event occurring in the studied population, indicating that preventive measures should be included in the home palliative care health team.